2022
DOI: 10.3991/ijet.v17i09.30919
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Teachers' Effective Teaching Behavior on Knowledge Transfer of Students in Online Teaching

Abstract: With the rapid development of information technology, the online education environment has become a reality. In specific online education practices, most teachers exhibit effective teaching behaviors by using multimedia technologies positively to stimulate the learning initiative of students, improve their learning performances, and promote their knowledge transfer. Based on theories of knowledge transfer and effective teaching behaviors, a measurement model that focuses on the effects of effective teaching be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For example, the use of the term or terms of events in Literature is not the same as the events used in the subject of History, while the motives in Literature are not the same as the mo-Open Journal of Social Sciences tives used in the legal system in the courts. Teachers who have knowledge in high content aspects emphasize more concepts, problem-solving and inquiry aspects in their subjects to the students (Magdeline & Zamri, 2014;Tan et al, 2022). Teachers who lack mastery and knowledge in the content aspect will emphasize more facts, rules, procedures and are too tied to lesson plans and textbooks alone.…”
Section: Content Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…For example, the use of the term or terms of events in Literature is not the same as the events used in the subject of History, while the motives in Literature are not the same as the mo-Open Journal of Social Sciences tives used in the legal system in the courts. Teachers who have knowledge in high content aspects emphasize more concepts, problem-solving and inquiry aspects in their subjects to the students (Magdeline & Zamri, 2014;Tan et al, 2022). Teachers who lack mastery and knowledge in the content aspect will emphasize more facts, rules, procedures and are too tied to lesson plans and textbooks alone.…”
Section: Content Knowledgementioning
confidence: 99%
“…Teaching techniques need to be diversified by teachers in order to attract more students to learn and even improve the thinking skills of students. The evidence, a study conducted by Che Zanariah and Fadzilah (2011) and Tan (2022) found that teachers are still weak in applying effective teaching techniques to create a conducive learning situation, attract students and make the process of teaching and facilitation in the classroom become more fun. Issues related to the use of ineffective teaching strategies and these students' learning problems can result in the main goals and objectives of the teaching and facilitation process not being fully achieved.…”
Section: Introductionmentioning
confidence: 99%
“…LMS can help educational units manage learning and organize content by engaging students to support the learning process [2] . Based on the statistics of the Kruskal-Wallis test, online learning platforms have a significant effect on knowledge transfer at the .05 level so that they can be a component of the effective teaching behavior [3].…”
Section: Introductionmentioning
confidence: 99%